Kinetics of Ethylene Epoxidation on a Promoted Ag/α‐Al2O3 Catalyst—The Effects of Product and Chloride Co‐Feeds on Rates and Selectivity. Issue 47 (8th June 2018) - Chen, Cha‐Jung; Harris, James W.; Bhan, Aditya
Abstract: The overall chloriding effectiveness factor ( Z *), defined as the ratio of ethyl chloride concentration in parts per million to the sum of ethylene and ethane concentration in mole percent multiplied by a weighting factor to account for their efficacy in removing chlorine‐adatoms from the surface, was used as a parameter to account for the effects of chlorine on the kinetics of ethylene epoxidation on a highly promoted 35 wt % Ag/α‐Al2 O3 catalyst. An increase in O2 order (≈0.7 to 1) and a decrease in C2 H4 order (≈0.5 to <0) with increasing Z * ( Z *=2.1, 3.4, 5.2, and 8.9) was observed implicating kinetic relevance of O2 activation on chloride‐promoted silver catalysts. Carbon dioxide co‐feed (1–5 mol %) was found to promote ethylene oxide selectivity as CO2 co‐feed reversibly inhibits CO2 synthesis rates (−0.6 order) more than ethylene oxide synthesis rates (−0.49 order) at all Z * values. Ethylene oxide and CO2 rates were found to be invariant with ethylene oxide (0–0.5 mol %) and acetaldehyde (0–1.7 ppm) co‐feeds, suggesting that there is minimal product inhibition under reaction conditions. A model involving a common reaction intermediate for ethylene oxide and carbon dioxide synthesis and two types of atomically adsorbed oxygen species—nucleophilic and electrophilic oxygen—is proposed to plausibly describe the observed reaction rate dependencies and selectivity trends as a function of the chloriding effectiveness. Abstract : Ethylene epoxidation challenged : Chloride and product co‐feeds modify the rates and selectivity of ethylene epoxidation for a highly promoted Ag/α‐Al2 O3 catalyst.